Systemic Candidiasis in Mice: New Insights From an Old Model - Jungnickel, Berit; Jacobsen, Ilse D. (Frontiers in Fungal Biology, 2022)
Animal models are essential to understand the pathophysiology of infections, to test novel antifungal compounds, and to determine the potential of adjunctive therapies, e.g. immune modulation. The murine model of systemic candidiasis induced by intravenous infection is technically straightforward, highly reproducible, and well-characterized. However, intravenous inoculation circumvents the necessity for the fungus to translocate across mucosal barriers, and the use of SPF mice that are immunologically naïve to Candida does not reflect the situation in human patients, in whom adaptive immune responses have been induced by mucosal colonization prior to infection. Therefore, mouse models that combine intestinal colonization and systemic infection have been developed, resulting in novel insights into host-fungal interactions and immunity. In this review, we summarize the main findings, current questions, and discuss how these might impact the translatability of results from mice to humans.